Accompagnement par les référents professionnels et professionnalisation des stagiaires en formation de moniteur éducateur - Nathalie Vidal (Presses universitaires de la Méditerranée, 2011)
How does the cooperative education, and in particular the process of professional refereesaccompanying the future social worker may contribute to its smoother professionalization? Based on a socio-psychological concept of representation, this study consists in intercrossing the trainee's point of view with the professional referee's one. In total, 4 referee's interviews have been conducted, 42 firs-tyear trainees' questionnaires and 37 second-year trainees' questionnaires have been performed. The data are analyzed using two lexicometric programs, known as ALCESTE and LEXICO. The results enhance the notion of « professionalized solidarity » and the nature in work of a « daily accompaniment by a multidisciplinary team » as prominent elements of the transmission between two professional generations.